2015
DOI: 10.1016/j.shaw.2015.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Noise-Induced Hearing Loss in the Police Force

Abstract: BackgroundNoise-induced hearing loss (NIHL) is a major preventable occupational health problem with 250 million people worldwide known to have disabling impairment of moderate to greater severity. The aims of the study are to estimate the prevalence of NIHL in the police force; and study its association with age, sex, duration of service (years), smoking and alcohol habits, use of hearing protective devices, as well as preexisting chronic diseases.MethodsA cross-sectional study was conducted on 543 police pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 26 publications
2
28
1
1
Order By: Relevance
“…In Press(In Press):e14258. and cutters was a little more than the standards, it caused a slight loss in the left ear; this is consistent with the studies of Bogre et al, Zhang et al, and Win et al; in these studies, an increase in sound pressure level led to an increase in hearing loss (4,23,27). Hearing loss did not occur in other groups due to lower sound pressure level than proposed standards by ACGIH and national standards in their work environment.…”
Section: -53supporting
confidence: 88%
See 1 more Smart Citation
“…In Press(In Press):e14258. and cutters was a little more than the standards, it caused a slight loss in the left ear; this is consistent with the studies of Bogre et al, Zhang et al, and Win et al; in these studies, an increase in sound pressure level led to an increase in hearing loss (4,23,27). Hearing loss did not occur in other groups due to lower sound pressure level than proposed standards by ACGIH and national standards in their work environment.…”
Section: -53supporting
confidence: 88%
“…Studies have shown that equivalent sound pressure levels continuously for more than 8 hours of exposure are two important parameters that describe the relationship between "constant noise and hearing loss" (4,(23)(24)(25). NoiseInduced Hearing Loss (NIHL) occurs along sensorineural hearing loss in high frequencies (between 3000 Hz and 6000 Hz) and the highest amount of hearing loss is usually seen around 4000 Hz (26,27). Noise-induced hearing loss occurs often during the first 10 to 15 years of exposure and at high frequencies and will mostly start at 4000 Hz frequency, yet its rate will vary depending on the individual and environmental factors (28).…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] This association is partly biased by the cumulative noise exposure inherent to an increasing age. Second, several studies on occupational NIHL 9,10,[12][13][14] have shown that men are more likely to develop NIHL than are women. For the same amount of occupational noise, Kovalova et al 13 observed significantly more NIHL in men than in women.…”
mentioning
confidence: 99%
“…Firearms are a common source of noise and hazardous noise levels associated with NIHL commonly occurs in the military and the police force during activities that involve firearm and pulse-induced explosions (Sulkowski et al 2017). A number of studies have reported abnormal levels of noise exposures in various occupations, including construction workers, farmers, railway workers, civil aviation workers, military personnel, firefighters, shipyard workers, offshore workers, healthcare workers, musicians, and police officers (Guida et al 2014, Win et al 2015. Previously published studies of hazardous noise exposures have focused on conventional occupations such as airport grounds staff and military personnel, while only a few studies have targeted less obvious professions such as police officers (Lesage et al 2009).…”
Section: Introductionmentioning
confidence: 99%